Ultrasmall metal nanoclusters as efficient luminescent probes for bioimaging - Xinyue Dou; Sariah Saalah; Chel-Ken Chiam; Jianping Xie; Coswald Stephen Sipaut @ Mohd Nasri (Royal Society of Chemistry, 2024)
Ultrasmall metal nanoclusters (NCs, <2 nm) have emerged as a novel class of luminescent probes due to their atomically precise size and tailored physicochemical properties. The rapid advancements in the design and utilization of metal NC-based luminescent probes are facilitated by the atomic-level manipulation of metal NCs. This review article explores (i) the engineering of metal NCs’ functions for bioimaging applications, and (ii) the diverse uses of metal NCs in bioimaging. We begin by presenting an overview of the engineering functions of metal NCs as luminescent probes for bioimaging applications, highlighting key strategies for enhancing NCs’ luminescence, biocompatibility and targeting capabilities towards biological specimens. Our discussion then centers on the bioimaging applications of metal NCs in subcellular organelles, individual cells, tissues, and entire organs. Finally, we offer a perspective on the challenges and potential developments in the future use of metal NCs for bioimaging applications.